Effects of high-pressure acclimatization on silver eel (Anguilla anguilla, L.) slow muscle contraction. - Rossignol, Orlane; Sebert, Philippe; Simon, Bernard (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2006)
International audience As the spawning migration of the eel is supposed to correspond to a long swimming activity at depth, patterns of slow red muscle contraction have been investigated in European silver eel (Anguilla anguilla L.) exposed for 3 weeks to 10.1 MPa hydrostatic pressure. The results show that pressure-acclimated eels (male and female) show a three-fold decrease in maximum isometric stress of twitch and tetanic contractions while time to peak force, time from peak force to 90% relaxation and ratio of twitch tension to tetanic tension remain unchanged. The observed modifications in slow red muscle mechanical properties do not impede the spawning migration of the eel and are possibly partially compensated by an improvement in the efficiency of oxidative phosphorylation. Effects of changes in membrane fluidity are also discussed.